Methodology for Interpreting Constitutional Legislation: Crucially Different or Much the Same? - Keyes, John (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2024)
This article considers whether the methodology for interpreting legislation that forms part of the Constitution of Canada is the same as or different from the methodology for interpreting other legislation. Former Chief Justice Dickson’s characterization of the interpretation of the Constitution as “crucially different from that of construing a statute” has had a significant effect on constitutional jurisprudence, but in what sense is it different and have these differences been overstated? This article begins by examining the features of constitutional legislation Dickson mentions and concludes they are neither unique to constitutional legislation nor found in all constitutional legislation. The article then considers constitutional decisions of Judicial Committee of the Privy Council and the Supreme Court of Canada interpreting and applying the Constitution Act, 1867 from the 19th century through to the 21st. On the basis of these decisions, the article concludes the elements of interpretive methodology Dickson identified, in relation to constitutional interpretation, apply to varying degrees, not only to constitutional texts, but also to non-constitutional legislation. The methodology for constitutional interpretation is essentially the same as that for interpreting other legislation. However, some constitutional legislation (notably provisions that have been frequently litigated) tends to attract particular elements of interpretive methodology and to that extent, it is distinctive. This article, and its focus on legislative interpretation, has its origins in an LLM thesis I prepared under the direction of Professor Archambault. It focused on the judicial review of delegated legislation, but it broadly ranged over many aspects of constitutional and administrative law that Professor Archambault prompted me to explore on my journey to provide a comprehensive picture of how the courts have supervised the exercise of delegated legislative power. I am deeply grateful for the expansive scope Professor Archambault allowed me and nourished with his guidance.